An analysis of the implementation of the operational alcohol and drug strategy 2007-2010 in the Marble Flats community : a case study - Johardien, Sharna (Department of Social Development, 2015)
This dissertation focused on two key issues that concern policy implementation in South Africa. Firstly, the researcher analysed the extent to which formal government policy implementation successfully occurs. Secondly, the researcher analysed the implementation of a specific policy, the Operational Alcohol and Drug Strategy 2007-2010 (OADS), through the use of a case study in the Ottery Marble Flats community, in order to illustrate the major issues concerning policy implementation in South Africa.